Quantifying thermal‐imager effectiveness for detecting bird nests on farms - Matthew D. Stephenson; Lisa A. Schulte; Robert W. Klaver (Wildlife Society Bulletin)
ABSTRACT We conducted a designed experiment to test whether having a thermal‐imaging camera available affected researchers' nest detection rates when searching for bird nests in cropland and grassland habitat in an agricultural landscape of Iowa, USA, in 2016. With known active nests present, naïve observers searched for nests with and without a thermal imager available. We did not find a difference in detection probabilities, although only a large difference would have been detectable with our sample size. Extraneous heat signatures from reflected solar radiation and dense vegetation were key factors limiting the usefulness of thermal imagers for locating nests. Published 2019. This article is a U.S. Government work and is in the public domain in the USA.